PENGARUH PELATIHAN, KOMPENSASI, DISIPLIN KERJA TERHADAP KINERJA KARYAWAN Studi Kasus di PT.Makmur Sejahtera Wisesa Tanjung Tabalong Anak perusahaan PT. Adaro Energy - Andria Marta; Tinik Sugiati; Maya Sari Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2020)
This research was conducted with the aim to find out whether there is an influence between training, compensation, and work discipline on the performance of the employees of PT. Makmur Sejahtera Wisesa This type of research is an explanation (explanatory research) using a questionnaire method, data analysis using multiple linear regression. The study population was employees of PT. Makmur Sejahtera Wisesa with a sample of almost the entire population or known as the saturated sample. The independent variables studied were training (X1), compensation (X2), and work discipline (X3), while the dependent variable was employee performance (Y). Based on the test results concluded that training has a significant effect on employee performance, compensation has a significant effect on employee performance, work discipline has a significant effect on employee performance